SANKSI PIDANA TERHADAP IBU KANDUNG YANG MENGAKIBATKAN MATINYA ANAK (STUDI PUTUSAN NOMOR 47.PID.SUS/2021/ PN.JKT.PST) - Kharisma Nabila Sapeva; Maria Silvya E. Wangga (Faculty of Law, Universitas Trisakti, 2023)
This research is about criminal sanctions imposed on biological mothers who act violently against their children by hitting them, resulting in the child's death. By reviewing decision No.47/Pid.Sus/PN.JKT.PST, the formulation of the research problem is whether the judge considers the punishment of the biological mother based on Article 80 paragraph (3) in conjunction with Article 76 C of Law no. 35 of 2014 in Decision no. 47/Pid.Sus/2020/Pn.Jkt is in accordance with the theory of the purpose of punishment. This research is of a normative juridical type which is descriptive in nature, through the use of secondary data with qualitative processing and drawing conclusions deductively. The results of his research showed that the judge did not consider the formulation of norms in Article 80 paragraph (3) in conjunction with Article 76 C of Law no. 35 of 2014 concerning child protection, namely the punishment increased by 1/3 so that the prison sentence for the perpetrator becomes 20 years. The conclusion from this research is that considering the sanctions that the judge imposed for the punishment of the biological mother in Article 80 paragraph (3) in conjunction with Article 76 C of Law no. 35 of 2014 does not match the theory of the purpose of punishment based on contemporary theory